Rodzina i ochrona życia poczętego na sesjach nadzwyczajnych ONZ (Kair plus pięć, Pekin plus pięć, Stambuł plus pięć) - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2008)
For me the history of the battle for fundamental values of our civilization began in the mid-1990s.At that time three major conferences took place: the International Conference on Populationand Development in Cairo in 1994, the 1995 World Conference on Women in Beijingand the Conference on Human Settlements in Istanbul in 1996. Surprisingly to most governmentsand international public opinion they became the battlefield of the war of ideas, which was especiallysignificant during the conferences in Cairo and Beijing. The liberal circles fiercely attacked traditionalvalues which constitute the basis of the international order. Among others, it was the right to liveand the institutional family which were especially attacked. There was even an attempt to replacethe word family with partnership.The Polish delegation for the conference in Cairo was instructed not only to support the idea ofstrengthening the family as a basic unit of society, but also to insist on accepting the common definitionof marriage as a union of a man and women and defend the position that abortion cannot be treated asa method of family planning or birth control.The discussion at the Cairo conference evolved into a battle for the right to kill unborn children asa method of family planning. Among the Holy See and Poland, it was the countries of Latin Americaand Muslim countries including African Muslim countries that spoke in defence of traditional values.At the Istanbul conference, also thanks to the Polish delegation, the family was acknowledged asa natural subject of housing policy.In the years 1999, 2000 and 2000 three UN special sessions were held: Cairo +5, Beijing +5and Istanbul +5. The Polish representation played an important role and the instruction for the Cairodelegation was fulfilled and remains valid.Although the documents of UN Special Sessions are not legally binding for the UN memberstates they are important for UN policy agendas e.g. economic help for third world countries. It ispossible to define the problem of famine as a one of the overpopulation and think of sending condomsto the starving as a solution.There is another consequence of such documents and their language: they influence the publicopinion and, after some time, they have an impact on rules of law in the UN member states.That consequence indicates the importance of that battle for the quality of life in the contemporaryworld.